Case Report: Treatment of Refractory Post‐Surgical Neuralgia With Erector Spinae Plane Block. Issue 5 (3rd January 2020) - Benkli, Barlas; Ansoanuur, George; Hernandez, Nadia
Abstract: Background: Peripheral nerve blocks (PNBs) are used for a wide spectrum of headache and facial pain disorders. The objective of this case report is to highlight the erector spinae plane (ESP) block, which has recently been reported to successfully treat headache. Case Presentation: A 70‐year‐old man with a history of mild to moderate headaches, previously ruptured aneurysm, and right pterional craniotomy and clipping of an anterior communicating artery aneurysm presented with exacerbation of chronic post‐surgical scalp pain and severe headache with nausea. Results of the physical examination were not consistent with cellulitis of the scalp, complete blood count and chemistry panel results were unremarkable, and imaging revealed an intact aneurysm clip. Given the severe unilateral throbbing pain with associated nausea, he was treated with a variety of migraine abortives and other pain medications without significant relief. ESP block was performed. He tolerated the procedure well without complications. His pain decreased to 2/10 from a baseline of 9 to 10/10 30 minutes after the procedure, and he was pain free the next day. Follow‐up revealed a return of his pain 1 to 2 weeks after the procedure, which prompted follow‐up with an outpatient pain management specialist. Conclusion: PNBs, ESP block in our case, can be a useful modality in managing chronic neuralgiform pain for treatment‐refractory patients. It can provide improvement in quality of life and spare the patient from medication side effects. In an inpatient setting, it can decrease length of stay that would otherwise be extended due to a trial of multiple medications until the pain was controlled. PNBs are used for a wide spectrum of headache and facial pain disorders. This case report highlights successful management of chronic neuralgiform pain with the ESP block, which has recently been reported to successfully treat headache. ESP block provided relief to the patient's neuralgiform pain that was refractory to multiple medications, resulting in decreased length of stay, fewer medication side effects, and improved quality of life. It also provided a window for initiation of long‐term pain medications.